2014
DOI: 10.11648/j.ijeedu.20140303.12
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Classrooms Transformed into Modern School Environments through Collaborative Action Research

Abstract: Collaborative teaching approach has confused teachers in Greece, who although generally argue in favour of this, however, state that they are unable to incorporate it into their daily teaching practice. Thus, collaborative action research, as a form of training, has been implemented to a group of teachers in order improvement to be achieved. The opinions and feelings of the participants are presented in the following article. Analyzing the facilitator's observation notes and the participants' interviews seems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Concerning Research Question (RQ), teachers' perceptions are characterized by a relatively satisfactory mean score (Μ=3.55) of collaborative culture. Therefore, it is found that teachers of primary schools lead and favor collaboration as their main philosophy, through which they reflect on their search for more effective ways to lead to school improvement, as previous research has shown (Lucas & Valentine, 2002;Ngnag, 2011;Kapachtsi, & Kakana, 2014).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Concerning Research Question (RQ), teachers' perceptions are characterized by a relatively satisfactory mean score (Μ=3.55) of collaborative culture. Therefore, it is found that teachers of primary schools lead and favor collaboration as their main philosophy, through which they reflect on their search for more effective ways to lead to school improvement, as previous research has shown (Lucas & Valentine, 2002;Ngnag, 2011;Kapachtsi, & Kakana, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…In terms of computer literacy and ICT, the evidence demonstrates the potential of an educational tool, especially in small rural schools, to provide meaningful education based on modern digital educational methods (Fykaris, 2012;Giannakos & Vlamos, 2012). Finally, their degree of satisfaction with their collaboration with the support structures, the local government, the school committee, the parents' association and the students are considered positive, perceptions that aim at changing-creating a school culture for an effective school (Kapachtsi & Kakana, 2014;Fulidi et al, 2017) and characterize the collaborative culture (Waldron & Mcleskey, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations